Disseminated T-cell lymphoma in a free-living white-winged duck (Asarcornis scutulata) under human care - Michelle F. O'Brien; Sara Shopland; Rosa Lopez Colom; Andrew F. Rich (Journal of Comparative Pathology, 2025)

EuPPollNet : A European Database of Plant‐Pollinator Networks - Jose B. Lanuza; Tiffany M. Knight; Nerea Montes‐Perez; Will Glenny; Paola Acuña; Matthias Albrecht; Maddi Artamendi; Isabelle Badenhausser; Joanne M. Bennett; Paolo Biella; Ricardo Bommarco; Andree Cappellari; et al. (Global Ecology and Biogeography, 2025)
Motivation Pollinators play a crucial role in maintaining Earth's terrestrial biodiversity. However, rapid human‐induced environmental changes are compromising the long‐term persistence of plant‐pollinator interactions. Unfortunately, we lack robust, generalisable data capturing how plant‐pollinator communities are structured across space and time. Here, we present the EuPPollNet (European Plant‐Pollinator Networks) database, a fully open European‐level database containing harmonised taxonomic data on plant‐pollinator interactions referenced in both space and time, along with other ecological variables of interest. In addition, we evaluate the taxonomic and sampling coverage of EuPPollNet, and summarise key structural properties in plant‐pollinator networks. We believe EuPPollNet will stimulate research to address data gaps in plant‐pollinator interactions and guide future efforts in conservation planning. Main Types of Variables Included EuPPollNet contains 1,162,109 interactions between plants and pollinators from 1864 distinct networks, which belong to 52 different studies distributed across 23 European countries. Information about sampling methodology, habitat type, biogeographic region and additional taxonomic rank information (i.e. order, family, genus and species) is also provided. Spatial Location and Grain The database contains 1214 different sampling locations from 13 different natural and anthropogenic habitats that fall in 7 different biogeographic regions. All records are geo‐referenced and presented in the World Geodetic System 1984 (WGS84). Time Period and Grain Species interaction data was collected between 2004 and 2021. Major Taxa and Level of Measurement The database contains interaction data at the species level for 94% of the records, including a total of 1411 plant and 2223 pollinator species. The database includes data on 6% of the European species of flowering plants, 34% of bees, 26% of butterflies and 33% of syrphid species at the European level. Software Format The database was built with R and is stored in ‘.rds’ and ‘.csv’ formats. Its construction is fully reproducible and can be accessed at: https://doi.org/10.5281/zenodo.14747448 .

Spatial and temporal variation in the prevalence of illegal lead shot in reared and wild mallards harvested in England - Emily A. Strong; Sarah L. Crowley; Julia L. Newth; Michelle F. O'Brien; Rosa Lopez Colom; Sean A. Davis; Ruth L. Cromie; Stuart Bearhop; Robbie A. McDonald (Environmental Pollution, 2024)

Stratification strength and light climate explain variation in chlorophyll a at the continental scale in a European multilake survey in a heatwave summer - Daphne Donis; Evanthia Mantzouki; Daniel F. McGinnis; Dominic Vachon; Irene Gallego; Hans‐Peter Grossart; Lisette N. de Senerpont Domis; Sven Teurlincx; Laura Seelen; Miquel Lürling; Yvon Verstijnen; Valentini Maliaka; et al. (Limnology and Oceanography, 2021)
To determine the drivers of phytoplankton biomass, we collected standardized morphometric, physical, and biological data in 230 lakes across the Mediterranean, Continental, and Boreal climatic zones of the European continent. Multilinear regression models tested on this snapshot of mostly eutrophic lakes (median total phosphorus [TP] = 0.06 and total nitrogen [TN] = 0.7 mg L −1 ), and its subsets (2 depth types and 3 climatic zones), show that light climate and stratification strength were the most significant explanatory variables for chlorophyll a (Chl a ) variance. TN was a significant predictor for phytoplankton biomass for shallow and continental lakes, while TP never appeared as an explanatory variable, suggesting that under high TP, light, which partially controls stratification strength, becomes limiting for phytoplankton development. Mediterranean lakes were the warmest yet most weakly stratified and had significantly less Chl a than Boreal lakes, where the temperature anomaly from the long‐term average, during a summer heatwave was the highest (+4°C) and showed a significant, exponential relationship with stratification strength. This European survey represents a summer snapshot of phytoplankton biomass and its drivers, and lends support that light and stratification metrics, which are both affected by climate change, are better predictors for phytoplankton biomass in nutrient‐rich lakes than nutrient concentrations and surface temperature.

Fundamental niche prediction of the pathogenic yeasts Cryptococcus neoformans and Cryptococcus gattii in Europe - Massimo Cogliati; Erika Puccianti; Maria T. Montagna; Antonella De Donno; Serdar Susever; Cagri Ergin; Aristea Velegraki; Mohamed S. Ellabib; Simona Nardoni; Cristina Macci; Laura Trovato; Ludovico Dipineto; et al. (Environmental Microbiology, 2017)
Summary Fundamental niche prediction of Cryptococcus neoformans and Cryptococcus gattii in Europe is an important tool to understand where these pathogenic yeasts have a high probability to survive in the environment and therefore to identify the areas with high risk of infection. In this study, occurrence data for C . neoformans and C . gattii were compared by MaxEnt software with several bioclimatic conditions as well as with soil characteristics and land use. The results showed that C . gattii distribution can be predicted with high probability along the Mediterranean coast. The analysis of variables showed that its distribution is limited by low temperatures during the coldest season, and by heavy precipitations in the driest season. C . neoformans var. grubii is able to colonize the same areas of C . gattii but is more tolerant to cold winter temperatures and summer precipitations. In contrast, the C . neoformans var. neoformans map was completely different. The best conditions for its survival were displayed in sub‐continental areas and not along the Mediterranean coasts. In conclusion, we produced for the first time detailed prediction maps of the species and varieties of the C . neoformans and C . gattii species complex in Europe and Mediterranean area.

Native fructose extracted from apple improves glucose tolerance in mice - C. Dray; A. Colom; C. Guigné; S. Legonidec; A. Guibert; F. Ouarne; P. Valet (Journal of Physiology and Biochemistry, 2009)

A halocin acting on Na+/H+ exchanger of Haloarchaea as a new type of inhibitor in NHE of mammals - J. L. Lequerica; J. E. O’Connor; L. Such; A. Alberola; I. Meseguer; M. Dolz; M. Torreblanca; A. Moya; F. Colom; B. Soria (Journal of Physiology and Biochemistry, 2006)

Psoas abscess in patients infected with the human immunodeficiency virus - V. Navarro Lpez; F. Lpez Garca; E. Gonzlez Escoda; J. Gregori Colom; A. Muoz Prez (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Heavy Metals in the Aerosols Collected at Two Stations in Mallorca (Spain) - J. Mateu; F. Bauzá de Mirabó; R. Forteza; V. Cerdà; M. Colom; M. Oms (Water, Air, & Soil Pollution, 1999)